Utilizing Electronic Medical Records to Standardize Handoffs in Academic Ophthalmology - Sun, Lynn W.; Stahulak, Andrea L.; Costakos, Deborah M. (Journal of Academic Ophthalmology, 2020)
Purpose Formalized handoff procedures have been shown to increase patient safety and quality of care across multiple medical and surgical specialties,1–4 but literature regarding handoffs in ophthalmology remains sparse. We instituted a standardized handoff utilizing an electronic medical record (EMR) system to improve care for patients shared by multiple resident physicians across weekday, weeknight, and weekend duty shifts. We measured efficiency, efficacy, and resident satisfaction before and after the standardized handoff was implemented.Methods Resident physicians surveyed were primarily responsible for patient care on consult and call services at two quaternary academic medical centers in a major metropolitan area. Patient care was performed in outpatient, emergency, and inpatient settings. Annual anonymous questionnaires consisting of 6 questions were used to collect pre- and postintervention impressions of the standardized EMR handoff process from ophthalmology resident physicians (9 per year; 3 preintervention years and 1 postintervention year). An additional anonymous postintervention questionnaire consisting of 12 questions was used to further characterize resident response to the newly implemented handoff procedure.Results Prior to implementation of a standardized EMR-based handoff procedure, residents unanimously reported incomplete, infrequently updated handoff reports that did not include important clinical and/or psychosocial information. Following implementation, residents reported a statistically significant increase in completeness and timeliness of handoff reports. Additionally, resident perception of EMR handoff utility, efficiency, and usability were comprehensively favorable. Residents reported handoffs only added a mean of 6.5 minutes to a typical duty shift.Conclusion Implementation of our protocol dramatically improved resident perceptions of the handoff process at our institution. Improvements included increased quality, ease-of-use, and efficiency. Our standardized EMR-based handoff procedure may be of use to other ambulatory-based services.
Keywords: handoff; handover; electronic medical record